Pengaruh Terapi Murrotal terhadap Kualitas Tidur Pasien Hipertensi di RSUD Kajen Kabupaten Pekalongan - Irma Islamiasih; Dwi Retnaningsih (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hypertension is a non-communicable disease characterized by elevated blood pressure above normal values and is often accompanied by sleep quality disturbances. Poor sleep quality can worsen hypertension by increasing sympathetic nervous system activity and physiological stress. Therefore, in addition to pharmacological therapy, safe, easy-to-apply, and effective non-pharmacological interventions are needed to improve sleep quality in hypertensive patients. One such non-pharmacological intervention is murottal therapy, which involves listening to recitations of the Holy Qur’an and provides relaxation and psychological calmness. This study aimed to determine the effect of murottal therapy on sleep quality in hypertensive patients at Kajen Regional Hospital, Pekalongan Regency. The research method used was a pre-experimental design with a one-group pre-test and post-test approach without a control group. The study subjects consisted of five patients who met the inclusion criteria. Sleep quality was measured before and after the intervention using the Pittsburgh Sleep Quality Index (PSQI). The murottal therapy intervention involved listening to the recitation of Surah Ar-Rahman for 15–30 minutes per day for three consecutive days. The results showed that all respondents experienced a decrease in PSQI scores, indicating an improvement in sleep quality after receiving murottal therapy. Murottal therapy was proven to have a positive effect as a non-pharmacological complementary therapy for hypertensive patients with sleep quality disturbances